Codes Switching and Codes Mixing of Sellers and Buyers in Traditional Markets: Case Study of Market Kampong Asembagus Situbondo - Fahmi Reza Alfani; Abdul Azizul Ghaffar; Muta’allim; Nawawi; Ali Wafi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
The process of buying and selling communication in Asembagus Traditional Market often experiences language contact because the sellers and buyers come from several ethnicities who have different languages ​​and cultures. This study aims to determine the form of code-switching and code-mixing speech between sellers and buyers in Asembagus Market, Situbondo. The method used in data collection is the engaging listening method with the technique of recording, taking notes, interviews and descriptive qualitative approaches. The results showed that there were 12 forms of code switching speech and 10 speech code mixtures between sellers and buyers at Asembagus Situbondo Market Kampong. Master more than one language and speakers try to build an atmosphere of speech with mixed languages, while the functions of code-switching and code-mixing speech used by sellers and buyers at Pasar Kampong are to adjust the social context and to smooth and build the communication process of bargaining, transactions, and interactions.